A Case Series Clinical Trial of a Novel Approach Using Augmented Reality That Inspires Self-body Cognition in Patients With Stroke: Effects on Motor Function and Resting-State Brain Functional Connectivity - Kaneko, Fuminari; Shindo, Keiichiro; Yoneta, Masaki; Okawada, Megumi; Akaboshi, Kazuto; Liu, Meigen (Frontiers in Systems Neuroscience, 2019)
Barring a few studies, there are not enough established treatments to improve upper limb motor function in patients with severe impairments due to chronic stroke. This study aimed to clarify the effect of the kinesthetic perceptional illusion induced by visual stimulation (KINVIS) on upper limb motor function and the relationship between motor function and resting-state brain networks. Eleven patients with severe paralysis of upper limb motor function in the chronic phase (7 men and 4 women; age: 54.7 ± 10.8 years; 44.0 ± 29.0 months post-stroke) participated in the study. Patients underwent an intervention consisting of therapy using KINVIS and conventional therapeutic exercise (TherEX) for 10 days. Our originally developed KiNvisTM system was applied to induce KINVIS while watching the movement of the artificial hand. Clinical outcomes were examined to evaluate motor functions and resting-state brain functional connectivity (rsFC) by analyzing blood-oxygen-level-dependent signals measured using functional magnetic resonance imaging. The outcomes of motor function (Fugle-Meyer Assessment, FMA) and spasticity (Modified Ashworth Scale, MAS) significantly improved after the intervention. The improvement in MAS scores for the fingers and the wrist flexors reached a minimum of clinically important differences. Before the intervention, strong and significant negative correlations between the motor functions and rsFC of the inferior parietal lobule (IPL) and premotor cortex (PMd) in the unaffected hemisphere was demonstrated. These strong correlations were disappeared after the intervention. Negative and strong correlation between the motor function and rsFC of the bilateral inferior parietal sulcus (IPS) significantly changed to strong and positive correlation after the intervention. These results may suggest that the combination approach of KINVIS therapy and TherEX improved motor functions and decreased spasticity in the paralyzed upper extremity after stroke in the chronic phase, possibly indicating contribution of embodied-visual stimulation. rsFC for the interhemispheric IPS and intrahemispheric IPL and PMd may be a possible regulatory factor for improving motor function and spasticity.